Pengaruh Kondisi Sosial Ekonomi, Pengetahuan dan Sikap Terhadap Kualitas Lingkungan Masyarakat Permukiman Sekitar Pasar di Kecamatan Tamalate Kota Makassar - Daud, Firdaus (Universitas Negeri Makassar, 2022)
Abstract. This study aims to analyze: 1) socioeconomic conditions, environmental knowledge, environmental care attitudes, and the quality of the residential environment of the community around the market d, 2) the influence of socioeconomic conditions and environmental knowledge simultaneously on the attitude of caring for the environment of the community around the market 3) the influence of environmental conditions Simultaneous socioeconomic, environmental knowledge and environmental attitudes on the environmental quality of the community around the market, 4) indirect influence (through environmental care attitudes) socio-economic conditions on the environmental quality of the residential community around the market in Tamalate subdistrict, Makassar City, 5) indirect influence ( through environmental awareness) environmental knowledge on the environmental quality of the residential community around the market in the Tamalate sub-district, Makassar City. This type of research is an expost-facto research which is correlational. The population in this study were all heads of families (KK) who were in settlements around the market within a 500 meter radius in Tamalate District, Makassar City. Determination of the sample size using the Isaac and Michael table with an error rate of 5%, the research sample obtained was 556 households. Sampling of 25% of 556 households, namely 139 samples The results of the study show: 1) The socio-economic conditions of the residential communities around the market are in moderate qualification. Community environmental knowledge in low qualifications, community environmental care attitudes in negative qualifications tend to be positive, and community environmental quality in high qualifications, 2) There is a significant influence of socio-economic conditions and environmental knowledge together on environmental care attitudes, 3) There is influence of environmental conditions socio-economic, environmental knowledge and environmental care attitudes together on environmental quality, 4) Indirectly socioeconomic conditions through environmental care attitudes have a significant effect on environmental quality, 5) Indirectly environmental knowledge through environmental care attitudes has a significant effect on quality environment. Based on the results of the study, the suggestions put forward by the researchers are as follows: 1) It is hoped that the Government, specifically the Makassar city government, will improve socio-economic conditions, environmental knowledge through education and training both at the city level and at the sub-district level, 2) the Health Service to always conduct direct outreach to the community to increase environmental knowledge, 3) It is expected that the people in the city of Makassar to actively participate in environmental management so that the environment is more qualified.Keywords: socio-economic conditions, knowledge, attitudes, environmental quality